2011
DOI: 10.1111/j.1751-7893.2011.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of parental mental illness: a literature review

Abstract: Despite references to pervasive knowledge gaps in the literature, significant information has been accumulated about children's experiences of parental mental illness. Considerable variability in research findings and tensions remain unresolved. For example, evidence is mixed as to children's knowledge and understanding of mental illnesses and how best to deploy resources to help them acquire optimal information. Furthermore, children's desire to be recognized as important to their parents' well-being conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 71 publications
(407 reference statements)
8
146
0
5
Order By: Relevance
“…A systematic review and meta-analysis by Siegenthaler et al (2012) across 13 trials involving over 1000 children found that formal interventions reduced the risk of children acquiring their own mental health disorder by 40 percent. Moreover, several studies suggest that parents, their children and families are more satisfied and find FFP more helpful than other models of practice (Espe-Sherwindt 2008; Gladstone et al 2011;Nicholson et al 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…A systematic review and meta-analysis by Siegenthaler et al (2012) across 13 trials involving over 1000 children found that formal interventions reduced the risk of children acquiring their own mental health disorder by 40 percent. Moreover, several studies suggest that parents, their children and families are more satisfied and find FFP more helpful than other models of practice (Espe-Sherwindt 2008; Gladstone et al 2011;Nicholson et al 2015).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…26 Çocukların hasta anne-babaları ile ilişkilerindeki iniş çıkışlar nedeniyle, günlük yaşamlarında duygularını düzenlemede sorunlar yaşadıkları, en sık yaşa-dıkları olumsuz duyguların korku ve üzüntü olduğu vurgulanmıştır. 27 Bazı anne-babaların ve ruh sağlığı uzmanlarının, genetik yüksek risk taşıyan bu çocukların sosyal olarak izolasyonu yeğle-dikleri izlenimine sahip olmalarına rağmen, çocukların bir kısmı arkadaşlarının duygusal destekleyici rolünü vurgulamakta, diğer bir kısmı ise arkadaşlıklarını 'karmaşık ve güç' olarak _____________________________________________________________________________________________________ nitelendirmektedirler. 27 Anne-babanın ruhsal bozukluğuna bağlı yaşanan güçlüklerin çocukları toplumsal olarak daha girişken ve bağımsız olmaya yönlendirdiğini bildiren bir çalışma da vardır.…”
Section: Discussionunclassified
“…27 Bazı anne-babaların ve ruh sağlığı uzmanlarının, genetik yüksek risk taşıyan bu çocukların sosyal olarak izolasyonu yeğle-dikleri izlenimine sahip olmalarına rağmen, çocukların bir kısmı arkadaşlarının duygusal destekleyici rolünü vurgulamakta, diğer bir kısmı ise arkadaşlıklarını 'karmaşık ve güç' olarak _____________________________________________________________________________________________________ nitelendirmektedirler. 27 Anne-babanın ruhsal bozukluğuna bağlı yaşanan güçlüklerin çocukları toplumsal olarak daha girişken ve bağımsız olmaya yönlendirdiğini bildiren bir çalışma da vardır. 28 Örneklemimizdeki YR grubundaki çocukların okul işlevselliklerinde kontrol grubuna göre anlamlı düşüş saptanmamıştır.…”
Section: Discussionunclassified
“…Ebeveynlerinden birinde ruhsal bozukluk bulunan çocuk ve yetişkinlerle yapılan çalışmalarda da bu çocukların bakım verme davranışlarında artış olduğu gözlenmektedir (Backer, Murphy, Fox, Ulph ve Calam, 2016;Brankin, 2014;Gladstone, Boydell, Seeman ve McKeever, 2011;Murphy, Peters, Jackson ve Wilkes, 2011;Stitt ve Reupert, 2014;Yarrow, 2011). Bu çalışmalarda, çocukların ebeveynlerini umutsuz, çaresiz gördüklerinde hem sözel (örn., doğru zamanda doğru "destekleyici" sözler söyleme) hem de sözel olmayan (örn., ebeveyne sarılma) yollarla onların yanında olmaya çalıştıkları ve duygusal olarak meydan okuyucu olabileceğini düşündükleri bir konuşmadan ya da kaygılarını onlara açmaktan kaçındıkları dikkati çekmektedir.…”
Section: Risk Faktörleri: Ebeveynleşmenin Sık Görüldüğü Aile öRüntüleriunclassified